Students' Mathematical Disposition with Blended Learning in Post Covid-19 - Dwi Desmayanasari; Desrina Hardianti; Deni Efendi; Tia Agnesa (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2022)
This study aims to analyze the mathematical disposition of online learning during the Covid-19 pandemic. The study type is descriptive quantitative, the subjects are 64 students of the education management program consisting of 18 males and 46 females. Based on the study result, the students mathematical disposition in blended learning during Covid-19 was in the high category. Of the six aspects of disposition measured, four aspects are classified as high, the aspect of confidence in using mathematics in solving problems is classified as moderate, while the aspect of appreciating the usefulness of mathematics in everyday life and other fields of science is very low. This study is a preliminary study to see the mathematical disposition of students during online learning. The aspect of appreciating the usefulness of mathematics needs special attention for further research where students have not fully recognized and realized the existence of mathematics in their daily activities and in other fields of science